Lake bed classification using acoustic data - Yin, K. Karen; Li, Xing; Bonde, John; Richards, Carl; Cholwek, Gary (Zielona Góra: Uniwersytet Zielonogórski)
As part of our effort to identify the lake bed surficial substrates using remote sensing data, this work designs pattern classifiers by multivariate statistical methods. Probability distribution of the preprocessed acoustic signal is analyzed first. A confidence region approach is then adopted to improve the design of the existing classifier.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka